DNA damage in cytologically normal urothelial cells of patients with a history of urothelial cell carcinoma - Gontijo, AMD; Marcondes, JPD; Elias, F. N.; de Oliveira, MLCS; de Lima, ROA; Salvadori, Daisy Maria Favero [UNESP]; de Camargo, JLV (Wiley-Blackwell, 2002)
In order to determine if patients with a history of previous urothelial cell carcinoma (UCC) but with current normal urinary cytology have DNA damage in urothelial cells, the single-cell gel electrophoresis (comet) assay was conducted with cells obtained by urinary bladder washings from 44 patients (28 with a history of previous UCC). Increased DNA damage was observed in cytologically normal urothelial cells of patients with a history of UCC when compared with referents with no similar history and after correcting the data for smoking status and age (P < 0.018). Increased DNA damage also correlated with the highest tumor grade, irrespective of time or course of the disease after clinical intervention (Kendall tau correlation, 0.37, P = 0.016). Moreover, aneuploidy, as assessed by DNA content ratio (DCR; 75th/25th percentile of total DNA fluorescence of 50 comets/patient) was unaltered by smoking status, but increased with UCC grade: 1.39 +/- 0.12 (median +/- 95% confidence interval; referents); 1.43 +/- 0.11 (Grade I UCC; P = 0.264, against referents); 1.49 +/- 0.16 (Grade II UCC; P = 0.057); 1.57 +/- 0.16 (Grade III UCC; P = 0.003). Micronucleated urothelial cells (MNC) were also scored on Giemsa-stained routine cytological smears and were found not to correlate with DNA damage or DCR. MNC frequencies were higher for patients with a history of UCC and/or smoking than referents with neither history, but there was no statistical difference between groups. Taken together, these results suggest that the normal-appearing urothelium of patients resected for UCC still harbor genetically unstable cells. (C) 2002 Wiley-Liss, Inc.
Keywords: tumor recurrence; cancer management; DNA damage; DNA content; micronucleated urothelial cells; transitional cell carcinoma